Care of HIV-Infected Pregnant Women in Maternal–Fetal Medicine Programs - Sklar, Peter A. (Hindawi Publishing Corporation, 2001)
Objective: To survey the evolution over the past decade of attitudes and practices of obstetricians in maternal–fetal medicine fellowship programs regarding the management of human immunodeficiency virus (HIV)-infected pregnant women. Methods: Directors of all 65 approved maternal–fetal medicine training programs were sent questionnaires, responses to which were to reflect the consensus among members of their faculties. Programs were stratified based upon the number of HIV-infected pregnant patients cared for in the previous year. Results: Responses reflect experience with over 1000 infected pregnantwomen per year, nearly one-quarter with advanced disease. Combination antiretroviral therapy was prescribed by all respondents, universally in the 2nd and 3rd trimesters. A three-drug regimen (often containing a protease inhibitor) was used more often by those who treated at least 20 HIV-infected pregnant patients per year than by those programs seeing a lower number of patients (80 vs 59%).Despite the known and unknown risks of the use of antiretrovirals during pregnancy, only half of all responding programs report adverse events to the Antiretroviral Pregnancy Registry; reporting was more common among the institutions seeing a higher number of patients (61 vs 45%). Seventy-eight percent of higher volume programs enroll their patients in clinical studies, usually multicenter, versus 35% of lower volume programs. Conclusions: Care for HIV² pregnant women has dramatically changed over the past decade. Antiretroviral therapy is now universally prescribed by physicians involved in maternal–fetal medicine training programs. Given limited experience with these agents in the setting of pregnancy, it is essential for maternal–fetal medicine practitioners to actively report on adverse events and participate in clinical trials.